Genetic variability and character association in fenugreek (Trigonella foenum-graecum L.) - B H Prajapati, D B Prajapati, Y Ravindrababu (Journal of Spices and Aromatic Crops, 2010)
Sixty four genotypes of fenugreek (Trigonella foenum-graecum) were evaluated for geneticvariability, correlation and path coefficient analysis at Jagudan (Gujarat). Phenotypic andgenotypic coefficients of variability were high for grain yield plant-1, number of pods plant-1and number of primary branches plant-1. Moderate heritability estimates along with highgenetic advance as percentage of mean were recorded for number of pods plant-1. Highheritability estimates along with moderate to low genetic advance as percentage of meanwere recorded for days to maturity and plant height. Grain yield was positively correlatedwith number of pods plant-1, number of seeds pod-1 and 1000 seed weight. Results of pathanalysis revealed that number of pods plant-1, days to 50% flowering and test weight hadhighest positive direct effects on grain yield. It was concluded that improvement of seed yieldin fenugreek is possible through selection for number of pods and seed weight throughnumber of grains and length of pods.